Nanometric lamination of zinc oxide nanofilms with gold nanoparticles for self-perceived periodontal disease sensors. (1st February 2022) - Bae, Garam; Kim, Minji; Lee, Ahyeon; Ji, Seulgi; Jang, Moonjeong; Yim, Soonmin; Song, Wooseok; Lee, Sun Sook; Yoon, Dae Ho; An, Ki-Seok
Abstract: Since methyl mercaptan (CH3 SH) concentration from exhaled breath increases marginally by the progress of periodontal disease, the design of a sensing materials that can selectively and accurately discriminate ppb-level CH3 SH among volatile sulfur compounds (VSCs) continue to be strongly demanded for the early diagnosis of periodontitis. Here, the primarily aim is to propose self-perceived-periodontal disease sensors by strategic nanometric lamination of 30 nm-thick ZnO nanofilms with 3 nm-thick Au nanoparticles (NPs) through the two-step process composed of atomic layer deposition and thermal evaporation techniques. Comprehensive microscopic and spectroscopic analysis corroborate the structural and chemical features of ZnO hybridized with Au NPs. The ZnO laminated with Au NPs optimized through size and density control enables to lead the significant enhancement of the gas sensing performance with 4.99% of gas response for 50 ppb of CH3 SH and a detection limit down to 50 ppb. It was highlighted that highly selective detection of ppb-level CH3 SH under a H2 S atmosphere was validated by the Au NP-incorporated ZnO hybrid sensors with reliable and reproducible gas sensing performance. Highlights: Periodontal disease sensors were realized using ZnO nanofilms with Au NPs. The structural and chemical features of the films were comprehensively examined. The Au NPs-incorporated ZnO sensors showed enhanced sensing performance. Highly selective detection of ppb-level CH3 SH was accomplished.